Nutrition Therapy in the Transition between Hospital and Home: An Investigation of Barriers - Mette Holst; Henrik Højgaard Rasmussen (Journal of Nutrition and Metabolism)
Aims and Objectives. This study aimed to investigate barriers for nutrition therapy in the transition between hospital and home and hereby to identify areas for potential improvements. Background. Though the focus on nutritional risk is improving in hospital, there seems to be less effort to maintain or even improve nutritional status after discharge and during the rehabilitation period. Design. Qualitative focus group interviews. Methods. Semistructured focus group interviews with experienced multiprofessional staff from hospital, home care, nursing homes, and general practise. The study was done in the county of Aalborg with about 280.000 inhabitants regarding homecare and general practise as well as Aalborg University Hospital, Denmark. Results. Interviews were generated with 41 professionals from hospital, general practise, and home care. Barriers identified between settings included the following aspects: economic, organisation, and education. The impression of professionals was that few patients are discharged with nutrition therapy, compared to who could benefit from nutrition therapy after discharge. Most often, reasons were a short in-hospital stay and lack of knowledge and interest. Moreover, lack of clinical guidelines throughout all settings, time consumption, lack of transparency regarding economy and workflows, and lack of assistance from experts regarding complicated nutritional problems were identified. Conclusions. Many barriers were found in hospital as well as in the community and general practise. These were most often practical as well as organizational. Improvements of clinical guidelines and instructions and improvement of knowledge and communication at all levels are needed. Relevance to Clinical Practise. This study emphasizes that responsibility needs to be taken for patients whom are still at nutritional risk at discharge, and even before hospitalization. Nurses and doctors in and outside hospital are in need of improved knowledge, standard care plans, and instructions.